EFFECT OF HIGH-DENSITY DIET FEEDING DURATIONS AND INITIAL CHICK WEIGHT CATEGORIES ON GROWTH, CARCASS, SERUM BIOCHEMISTRY AND IMMUNE RESPONSE OF COMMERCIAL BROILERS - H. A. Akram; S. Mehmood; F. Hussnain; Saima; J. Hussain; M. T. Khan (Journal of Animal and Plant Sciences, 2022)
The objective of this study was to evaluate the effect of feeding high density diet for different durations on growth performance, carcass characteristics and immune response of commercial broilers affected by initial chick weight categories. A total 600 1-d-old, broiler chicks (Ross 308) were randomly placed according to a completely randomized design under a factorial arrangement, with 03 body weight categories namely C, B, A (i.e., 31-34 g, 35-38 g, 39-42 g, respectively) and 04 high-density diet feeding durations (0, 5, 10, and 15 days) during the starter phase. Each treatment was replicated five times, having 10 birds apiece. The results revealed that the chicks of the A category had higher body weight, better feed conversion ratio and dressing percentage while feed intake and cut-up yield remained unaffected with chick weight categories. The chicks belonging to the higher body weight category also showed a higher antibody titer against Newcastle disease. The birds fed on high protein diet for 15 days showed higher final weight, best feed conversion ratio, the highest percentage of carcass yield, and the highest immunity against Newcastle disease. However, there was a slight difference between the birds fed on high protein diet for 10 days and 15 days. The birds belonging to large chick categories resulted in maximum profit when fed on high protein diet for 10 days whereas the birds belonging to small categories suffered with a greatest loss when fed on a control diet. Therefore, it was concluded from the results that birds having higher initial weight will ultimately have higher weight at slaughter age. In concern to feeding regimes, the birds fed with high density diet remained most economical. It is also concluded that the weight of chicks with lower initial body weight can be compensated till slaughter age by feeding them with high density diet during starter phase.
Keywords: High density diet; chick weight; performance; economics